2018
DOI: 10.1037/trm0000151
|View full text |Cite
|
Sign up to set email alerts
|

Mental health outcomes in military veterans: A latent growth curve model.

Abstract: Some research has suggested that income and mental health are related in the general population. In the present study, we examined the relationship between income and mental health among military service members and veterans. Researchers examined veteran respondents from the 2011–2014 Behavioral Risk Factor Surveillance System (2011, n = 64,594; 2012, n = 59,870; 2013, n = 61,505; 2014, n = 62,120), comparing the frequency of poor mental health days in the last 30 days and income levels. Individual-level data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The results are also in line with Wienert, Schwarz [ 68 ], supporting the conclusion that work-related medical rehabilitation benefited the quality of life and mental health in cancer patients. Furthermore, the LGCM was used, and the results found that military veterans’ mental health demonstrated a quadratic change [ 69 ], and the workers’ psychological well-being showed linear changes [ 70 ]. It is possible that mental health is unstable and impressionable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are also in line with Wienert, Schwarz [ 68 ], supporting the conclusion that work-related medical rehabilitation benefited the quality of life and mental health in cancer patients. Furthermore, the LGCM was used, and the results found that military veterans’ mental health demonstrated a quadratic change [ 69 ], and the workers’ psychological well-being showed linear changes [ 70 ]. It is possible that mental health is unstable and impressionable.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore the role of rehabilitation treatment, a control group and an experimental design would be interesting in future studies to shed more light on specific intervention variables and how they influence related health outcomes. Fourth, it is unknown whether the findings of this study could be applied to other populations, such as workers with job burnout [ 88 ], unemployed persons [ 89 , 90 ], or military personnel [ 69 , 91 ]. Further research could generalize the conclusions among other populations to explore the internal mechanisms of the mental and physical changes and lay a theoretical foundation for further intervention research, such as interventions for occupational health [ 92 ].…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Thus, other variables may need to be considered in the future studies, such as other traumas including natural disasters, accidents, or disease (Infurna, Gerstorf, & Ram, 2013; Knight, Gatz, Heller, & Bengtson, 2000), smoking (Byers et al, 2012), and alcohol use (Brennan, SooHoo, Lemke, & Schutte, 2016) that can be associated with poorer mental health during adulthood. Moreover, research shows that socioeconomic factors such as income (McDaniel, Thomas, Albright, Fletcher, & Shields, 2018) and personal characteristics such as optimism (Thomas, Britt, Odle-Dusseau, & Bliese, 2011) influenced the effect of combat exposure on mental health outcomes. These variables should be taken into consideration in future studies.…”
Section: Discussionmentioning
confidence: 99%